'Wherever you are, my son, wait for me.' study on medically assisted reproduction. (20th October 2021) - Napolitani, M; Lorenzini, L; Valentini, V; Alaimo, L; Nante, N
Abstract: Introduction: In Italy the use of Medically Assisted Procreation (MAP) is increasingly frequent also because the mean age at which Italian women have their first child has increased in recent decades (31.8 years in 2017) and it is more difficult to have a child for an older woman. The aim of this study was evaluate the maternal and neonatal outcomes of MAP and compare them with those of natural pregnancies. Methods: The cross-sectional study was performed during the period January 2015-June 2019. All women that gave birth in the Hospital of Siena were included. The sample was divided in two groups (Natural pregnancy/MAP Pregnancy). The outcome variables were: maternal age, number of foetus, type of childbirth, timing of the birth, Apgar Index and necessity of hospitalization in neonatal intensive therapy unit (NITU) or resuscitation. The statistical analysis was performed with Stata 12. Results: In total 5066 females were included (4.5% MAP pregnancy). The average age (±SD) of females was 32, 9±5, 56 (min 14-max 61). The mean age (±SD) of women with PMA was significantly higher 38.7 ± 5.7 vs. 32.6± 5.4 of those who had natural pregnancy. In PMA Pregnancy there was a higher probability of multiple pregnancy (OR = 16.13; 95% CI 10.38-25.07; p < 0.001), Caesarean Section (OR:4, 54; 95% CI 3.28-6.31; p < 0, 001) and preterm birth (OR 3.79; 95% IC 2.80-5.14; p < 0.001). Apgar index at the first minute was significantly lower in children born from pregnancies from MAP (8, 6 ±1, 4 vs, 9 ±1, 4 p < 0.01), the difference was significant even in the 5th minute (9, 6 ±0, 7 vs. 9, 8 ±0, 6 p < 0.01). Children born by MAP Pregnancy had higher probability of hospitalization in Neonatal Intensive Care (OR = 3.12; 95% CI 2.12-4.59; p < 0.001). Conclusions: In our sample we found that MAP is used by women with older average age and it is associated with less favourable maternal and neonatal outcomes than those from natural conception. Key messages: In Italy the use of Medically Assisted Procreation (MAP) is increasingly frequent because it is more difficult to have a child for an older woman. In our sample we found that MAP is used by women with older average age and it is associated with less favourable maternal and neonatal outcomes than those from natural conception.